Question

Activity 2 Simplify the following WITHOUT the use of a calculator: \( 2.1 \frac{\tan \left(180^{\circ}+x\right) \cdot \cos \left(360^{\circ}-x\right)}{\sin (180-x) \cdot \cos \left(90^{\circ}+x\right)+\cos \left(540^{\circ}+x\right) \cdot \cos (-x)} \)

Ask by Dunn Graham. in South Africa
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The simplified expression is –2.1 sin x.

Solution

We wish to simplify the expression   2.1 · [tan(180° + x) · cos(360° – x)]     ————————————————————————————————————     [sin(180° – x) · cos(90° + x) + cos(540° + x) · cos(–x)] Step 1. Simplify the numerator. • Recall that tan(θ + 180°) = tan θ. Thus,   tan(180° + x) = tan x. • Cosine has period 360°. Also, cos(θ) is even so cos(–x) = cos x. Therefore,   cos(360° – x) = cos(–x) = cos x. So the numerator becomes:   tan x · cos x. Step 2. Simplify the denominator. The denominator has two parts. We simplify each term: Term A: sin(180° – x) · cos(90° + x)   • sin(180° – x) = sin x.   • cos(90° + x) = – sin x     (since cos(90° + θ) = – sin θ). Thus, Term A = sin x · (– sin x) = – sin² x. Term B: cos(540° + x) · cos(–x)   • Notice that 540° = 360° + 180°. Using the periodicity of cosine,     cos(540° + x) = cos(180° + x) = – cos x     (because cos(180° + θ) = – cos θ).   • Also, cos(–x) = cos x. Thus, Term B = (– cos x) · cos x = – cos² x. Adding both terms in the denominator:   Denom = – sin² x – cos² x = – (sin² x + cos² x). Since sin² x + cos² x = 1, we have   Denom = –1. Step 3. Write the simplified expression. The original expression becomes:   2.1 · (tan x · cos x) / (–1) = –2.1 · (tan x · cos x). Step 4. Final simplification. Recall tan x = sin x / cos x. Then:   tan x · cos x = (sin x / cos x) · cos x = sin x. Thus, the entire expression simplifies to:   –2.1 · sin x. Answer: –2.1 sin x.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To simplify the given expression, we can start by applying some trigonometric identities. 1. **Understanding the Angles**: - \(\tan(180^{\circ} + x) = \tan(x)\) because tangent has a period of \(180^{\circ}\). - \(\cos(360^{\circ} - x) = \cos(x)\) because cosine has a period of \(360^{\circ}\). - \(\sin(180 - x) = \sin(x)\) (sine is positive in the second quadrant). - \(\cos(90^{\circ} + x) = -\sin(x)\). - \(\cos(540^{\circ} + x) = \cos(180^{\circ} + x) = -\cos(x)\) (cosine changes sign). - \(\cos(-x) = \cos(x)\) (cosine is an even function). Now, substituting these identities into the expression gives: \[ 2.1 \frac{\tan(x) \cdot \cos(x)}{\sin(x) \cdot (-\sin(x)) + (-\cos(x)) \cdot \cos(x)} \] This simplifies to: \[ 2.1 \frac{\tan(x) \cdot \cos(x)}{-\sin^2(x) - \cos^2(x)} \] The term \(-\sin^2(x) - \cos^2(x)\) simplifies to \(-1\) (using the Pythagorean identity). This yields: \[ 2.1 \frac{\tan(x) \cdot \cos(x)}{-1} = -2.1 \tan(x) \cdot \cos(x) \] Now, we can utilize the identity \(\tan(x) = \frac{\sin(x)}{\cos(x)}\): Thus, \( -2.1 \tan(x) \cdot \cos(x) = -2.1 \frac{\sin(x)}{\cos(x)} \cdot \cos(x) = -2.1 \sin(x) \). So the final simplified expression is: \[ -2.1 \sin(x) \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy